Additionally, the Author Examines the Management, Prognosis, and Complications Associated with RBBB. - Ilham, Lalu Fahril; Haribowo, Pendy Wastu (Lombok Medical Journal, 2025)
Right Bundle Branch Block (RBBB) is an abnormality in the physiological electrical conduction system of the heart, resulting from a blockade of the right bundle branch. The global incidence of RBBB is estimated to be approximately 0.8% annually. Typically, RBBB is considered a mild finding that does not increase the risk in otherwise healthy individuals without structural heart disease. However, RBBB may also be indicative of myocardial disease and has been identified as a predictor of mortality in certain populations. This literature review aims to summarize the pathophysiology and clinical approach to RBBB, with a particular focus on echocardiography (ECG) examinations, based on literature sourced from PubMed, Google Scholar, and additional manual searches conducted between 2016 and 2021. Additionally, the author examines the management, prognosis, and complications associated with RBBB.